ISL-1: a new potential marker of stem/progenitor cells in the developing human uterus - Flaviana Cau; Maria Carolina Botta; Laura Vinci; Clara Gerosa; Ester Sorrentino; Giancarlo Senes; Flaminia Bardanzellu; Sara Aversa; Francesco Ronchi; Cristiana Bellan; Gavino Faa (Hygeia Press di Corridori Marinella, 2019)
The human uterus is a highly dynamic organ with peculiar plasticity and marked reproductive ability, due to the presence of a vast number of multiple stem/progenitor cell types, including endometrial, stromal and vascular progenitor cells. Conflicting results have been published regarding which uterine population might represent the real stem/progenitor cell fraction in terms of in vivo stem cell activity. Human endometrial side population (ESP) cells were shown to differentiate into multiple endometrial lineages in the stem cell niche provided by whole endometrial cells, suggesting that ESP cells might represent the most important stem/progenitor cells responsible of the cyclical regeneration of the endometrium throughout a woman's reproductive life. This study was aimed at analyzing the localization, composition, and occurrence of stem cell niches in the human fetal uterus at different stages of development. To this end, the whole uterus was obtained at autopsy by 12 human fetuses and newborns, ranging in gestational age from 12 up to 39 weeks of gestation. Tissue paraffin sections were immunostained with antibodies against insulin gene enhancer protein (ISL-1), a transcription factor previously utilized as a marker of stem/progenitor cells in the pancreas, heart and nervous system. Reactivity for ISL-1 was detected in both epithelial and stromal uterine precursors, at all gestational ages, allowing the detection of uterine progenitor cells. The loss of reactivity for ISL-1 in some stromal cell precursors was interpreted as a sign of differentiation. These preliminary data indicate ISL-1 as a useful marker for the detection of stem/progenitor cells in the human fetal endometrium. Further studies are needed to verify the utility of ISL-1 as a marker of stem/progenitor cells in the adult endometrium.